EFEKTIVITAS BLENDED LEARNING TIPE FLIPPED CLASSROOM TERHADAP KEMAMPUAN PEMAHAMAN MATEMATIS SISWA SMP - Nurdani, Agus; Nur, Iyan Rosita Dewi (Universitas Bhinneka PGRI, 2024)
This study aims to measure the effectiveness of the flipped classroom blended learning model on the mathematical understanding abilities of junior high school students. The research adopts a quantitative approach with a quasi-experimental design involving two classes at SMPN 3 Karawang Barat. Class VIII-B, serving as the experimental group, received instruction using the flipped classroom model, while class VIII-A, serving as the control group, was taught using conventional teaching methods. Data were collected through pretests and posttests that measured the students' mathematical understanding abilities. The results indicated a significant improvement in the mathematical understanding abilities of the students in the flipped classroom model compared to those in the conventional teaching methods. This conclusion was derived from data analysis using the t-test, which showed a significant difference between the students who were taught using the flipped classroom model and those who were taught using conventional methods in terms of their improvement in mathematical understanding abilities. Further analysis using N-gain and effect size tests was conducted, This study concludes that the flipped classroom blended learning model can be an effective alternative to enhance the mathematical understanding abilities of junior high school students.